Histological Analysis of Intestinum Tenue Rabbit Atherosclerosis Model - Vista Budiariati; Ariana .; Teguh Budipitojo (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Atherosclerosis is a vascular disease that occurs as a result of a progressive inflammatory response in blood vessels. The method of inducing atherosclerosis with the rabbit animal model can be done by modifying the high-fat diet which can lead to hypercholesterolemia within a few days to the inducement of atheromatic lesions. This study was conducted to analyze the histology of the small intestine in a group of rabbits fed with standard diet and atherosclerosis model of rabbits fed with atherogenic diet. The results of morphometry analysis in the small intestine showed that the duodenal submucosa in group B was wider than group A, while the length of jejunal villi in group B was shorter than group A. Changes in the intestine were also followed by changes in the cell population. The number of goblet cells in the duodenum was less in group B compared to group A, but the number of goblet cells in the jejunum was actually more in group B than in group A. Further research is needed to determine the mechanism that causes this change so that it can support modeling of atherosclerosis in rabbits according to the pathophysiology and pathogenesis of diseases that occur in humans.